Arranging for strings - Rabson, Mimi (Berklle Press, 2018)
Learn to use strings in your compositions and arrangements! From romantic chord pads to powerful grooves to gut-wrenching passionate melodies, strings do it all. This book presents time-tested techniques and contemporary developments in writing and arranging for strings. You'll learn strategies for authentic writing in many different styles and find ideas to take your personal sound forward. Discover voicings that work best for each project and explore the intricacies of bowing. Hear articulation approaches from pads to chopping in the online audio examples. See how other composers have used strings to heighten the impact of their music in the written examples. Make your work stand out with the drama and depth that well informed string writing can bring.